Pendampingan Ke SMA Pax Patriae Untuk Membangun Ekonomi Kreatif di Era Pandemi - Anastasia Santi; Angelique Johan; Felicia Anggono; Janson Angriawan Aslan; Priscilla Netania; Yeremia Sutanto (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2023)
A creative economy is related to human creativity that can generate profits and is considered to improve the national economy. One area of the creative economy is the fashion sector, which includes clothing such as T-shirts, accessories, hats, wallets, and other souvenirs. Becoming a well-known brand takes a long time because the most difficult thing is building public trust that the products sold are of good quality. However, most businesses engaged in the creative economy have good long-term prospects. This can be seen from the benefits obtained because the products offered usually will not run out in time because they are durable and have endless creative ideas. Therefore, it is very interesting for us to discuss and educate the public about the importance of the creative economy.